(3EaTGA GdSQ GdeUQaj Hjf GdMXQ h GdGHGMI (B:s (3OQGSI ebGQfI (B/s - (3SdGeI, eMeO YHO GdMj GHQGgjes ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2012)
(3GdEdJRGe HGdSQ GdeUQaj(B- (3eGgjI GdEdJRGe HGdSQ GdeUQaj h CgejJg h JWhQg hfWGbg(B- (3GdENdGd HGdEdJRGe HGdSQ GdeUQaj(B- (3BKGQ GdENdGd HGdEdJRGe HGdSQ GdeUQaj(B- (3GdeSDhdjI GdbGfhfjI ef EaTGA GdSQ GdeUQaj(B- (3GdESJKfGAGJ GdJj jHGM ajgG cTa CSQGQ GdYejds
Keywords: (3GdBOGH GdbGfhfjIs; (3GdHfhc(B- (3GdSQjIs